Histórias em quadrinhos traduzidas (e no prelo) para polaco: Abordagem histórica e teórica na área dos estudos de tradução (Studia Iberystyczne, 2019)
Brazilian Comic Books Translated (and Being Currently Translated) into Polish. Historical and Theoretical Approach in the Area of Translation StudiesComic strips (HQs) translated and published in Polish (PT-BR → PL) count 14 volumes (albums). Several conditions that influence the target text result from the exceptionality of the medium as well as from the linguistic worldview (JOS - językowy obraz świata) of the story itself, and as such can serve as a living example to formulate some rules that shape the final text in the case of comics. The present article aims to objectify the empirical experience of the translation process through the methodological approach that combines introspection (cognitive psychology), translation theory and comics theory. The reflection that emerges from this connection joins the perspective of two authors (translator + researcher [in the area of TS and comics]) and allows to self-define, describe and solve in an objective way the major translation problem that are found in the translated HQs.